2022
DOI: 10.3390/microorganisms10050957
|View full text |Cite
|
Sign up to set email alerts
|

Is the Pendulum of Antimicrobial Drug Resistance Swinging Back after COVID-19?

Abstract: The COVID-19 pandemic may have had an effect on antimicrobial resistance. We compared the prevalence of ESKAPE multidrug-resistant (MDR) bacterial infections in COVID-19 affected/unaffected patients admitted to intensive care units (ICU) or infectious disease units at the “Mater Domini” University Hospital of Catanzaro between 1 March 2020 and 31 July 2021. Moreover, an analysis of MDR rates in ICU comparing the pre-pandemic period with the pandemic period was performed, and the possible consequence on in-hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
3
19
0
2
Order By: Relevance
“…We found that the overall MDR-GN BSI incidence density was lower in the CoV patients than the no-CoV ones, although the rate per pathogen showed an increase in the CRAB incidence in the former group of patients, albeit not significant. Several studies reported a decrease or no change in the incidence of MDRO colonization or infection in ICUs during the COVID-19 pandemic period, as with our findings [9,21,24,25], while other studies observed a significant increase in MDRO infections [15,20,22] or an increase only in a specific subgroup of patients with colonization or infection due to CRAB, as our study showed [9,21]. The change in our local epidemiology is associated with some outbreaks of CRAB infection during the observation period which reduced the K. pneumoniae incidence density.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that the overall MDR-GN BSI incidence density was lower in the CoV patients than the no-CoV ones, although the rate per pathogen showed an increase in the CRAB incidence in the former group of patients, albeit not significant. Several studies reported a decrease or no change in the incidence of MDRO colonization or infection in ICUs during the COVID-19 pandemic period, as with our findings [9,21,24,25], while other studies observed a significant increase in MDRO infections [15,20,22] or an increase only in a specific subgroup of patients with colonization or infection due to CRAB, as our study showed [9,21]. The change in our local epidemiology is associated with some outbreaks of CRAB infection during the observation period which reduced the K. pneumoniae incidence density.…”
Section: Discussionsupporting
confidence: 89%
“…Of interest, the burden of A. baumannii infections in CoV patients has been described worldwide with several outbreaks reported [ 19 ]. This so-called “little pandemic” within the huge COVID-19 pandemic represents a matter of concern as the greatest threat to COVID-19 patients admitted to ICUs [ 9 , 20 , 21 , 22 , 26 ]. However, new observational studies are needed to assess the real impact of CRAB invasive infections on mortality in critically ill CoV patients [ 20 , 22 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent decades, an increasing number of antibiotic-resistant bacterial strains have been reported. Therefore, conventional antibiotic therapy is often ineffective [ 1 , 2 , 3 ], leading to the search for new treatment options for bacterial infectious diseases. Several possibilities exist to overcome bacterial resistance to antibiotics; for example, the development of new effective antibiotics [ 4 ]; the testing of the antimicrobial effect of natural substances, such as herbal products [ 5 , 6 ], honey [ 7 ] or wine products [ 8 ]; the use of photodynamic inactivation [ 9 ] or the quorum-quenching approach [ 10 ]; or therapy that modulates the patient’s own immunity using immunomodulators of microbial origin or therapeutic autovaccines prepared from the patient’s own strains [ 11 ].…”
Section: Introductionmentioning
confidence: 99%